Use of Tense-Aspect Forms in Cordis Project Reports - Jana Kuzmina (Baltic Journal of English Language, Literature and Culture)
For several recent decades the Council of Europe and various European authorities have been encouraging various European universities and other institutions to unite research activities resulting in the creation of partnerships with a conventialised genre network of calls for projects, guidelines for proposals and databases of project documentation. Along with Latvia acting in political, economic and social arenas of the European Union, it has also been actively involved in research consortia as coordinator and participant, therefore, setting new objectives for communicative competence development of scholars and project managers in order to reflect the discursive practices. In view of this, the present cross-sectional empirical investigation is intended to explore the written genre of Community Research and Development Information Service (CORDIS) periodic (status) and closure (results in brief) project reports as fundamental documents to account for research results in various economically and socially significant spheres. The selected research methodology is a descriptive case study, involving genre and discourse analysis. The obtained results claim that reports have a rigid generic macro-structure. It explains the use of the selected tense-aspect forms to express the communicative aim in both types of reports; however, periodic reports demonstrate higher variation due to the involvement of a different discourse community. The significance of the study lies in the scarcity of previous research on this genre and wide application of research findings to support the discourse community of researchers.